(untitled) - Osborn, Richard K. (Singapore, 1988)
This is book introduction about the simple shell model, introduction to reaction rates, neutron-nuclear cross-sections, some applications, a hamiltonian for nonrelativistic, spinless charged paticles in the presence of electromagnetic fields...
Keywords: Quantum theory,Nuclear engineering,Lý thuyết lượng tử,Kỹ thuật hạt nhân